Hermeneutika Hadits Fatima Mernissi (Implikasi terhadap Hadis Kepemimpinan Perempuan) - Musdalipa Musdalipa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This paper aims to explore the hermeneutics proposed by Fatima Mernissi in reading a hadith, especially those related to the hadith of female leadership. In this case, the hadith narrated by Abu Bakrah's companion stated that